Ответ:
Пошаговое объяснение:
1. log₇log₄log₃(x-7)=0 ОДЗ: x-7>0 x>7.
log₄log₃²(x-7)=1
log₃²(x-7)=4¹=4
log₃(x-7)=2 x-7=3² x₁=16
log₃(x-7)=-2 x-7=3⁻² x₂=7¹/₉.
2. lg(x+2)=lg5-lg(x-2)
lg(x+2)=lg(5/(x-2))
ОДЗ: x+2>0 x>-2 x-2>0 x>2 x∈(2;+∞)
x+2=5/(x-2)
x²-4=5
x²=9
x₁=3 x₂=-3 ∉ ОДЗ. ⇒
Ответ: x=3.
3. lg²x+2*lgx=3 ОДЗ: x>0
lg²x +2*lgx-3=0
Пусть lgx=t ⇒
t²+2t-3=0 D=16 √D=4
t₁=lgx=1 x₁=10
t₂=lgx=-3 x₂=10⁻³=0,001.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Пошаговое объяснение:
1. log₇log₄log₃(x-7)=0 ОДЗ: x-7>0 x>7.
log₄log₃²(x-7)=1
log₃²(x-7)=4¹=4
log₃(x-7)=2 x-7=3² x₁=16
log₃(x-7)=-2 x-7=3⁻² x₂=7¹/₉.
2. lg(x+2)=lg5-lg(x-2)
lg(x+2)=lg(5/(x-2))
ОДЗ: x+2>0 x>-2 x-2>0 x>2 x∈(2;+∞)
x+2=5/(x-2)
x²-4=5
x²=9
x₁=3 x₂=-3 ∉ ОДЗ. ⇒
Ответ: x=3.
3. lg²x+2*lgx=3 ОДЗ: x>0
lg²x +2*lgx-3=0
Пусть lgx=t ⇒
t²+2t-3=0 D=16 √D=4
t₁=lgx=1 x₁=10
t₂=lgx=-3 x₂=10⁻³=0,001.
(1/log₂x)*(1/log₂2x)=1/log₂4x
log₂4x=log₂x*log₂2x
log₂4+log₂x=log₂x*(log₂2+log₂x)
log₂2²+log₂x=log₂x*(1+log₂x)
2+log₂x=log₂x+log₂²x
log₂²x=2
log₂x=√2 x₁=2^√2.
log₂x=-√2 x₂=2^(-√2)=1/2^√2.
x^(3-lg(x/3))=30²
log₁₀x^(3-lg(x/3))=log₁₀30²
(3-lg(x/3)*lgx=2*lg30
(3-(lgx-lg3))*lgx=2*(lg10+lg3)
(3-lgx+lg3)*lgx=2+2*lg3
3*lgx-lg²x+(3+lg3)*lgx=2+2*lg3
lg²x-(3+lg3)*lgx+(2+2*lg3)=0
t²-(3+lg3)*t+(2+2*lg3)=0
D=(3+lg3)²-4*(2+lg3)=9+6*lg3+lg²3-8-8*lg3=lg²3-2*lg3+1=(lg3-1)²
√D=+/-(lg3-1) ⇒
t₂=lgx=(3+lg3-(lg3-1))/2=(3+lg3-lg3+1)/2=4/2=2 ⇒ x₁=t₁=lgx=(3+lg3+lg3-1)/2=
= (2+2*lg3)/3=1+lg3=lg10+lg3=lg30
lgx=lg30 x₁=30.
t₂=lgx=(3+lg3-(lg3-1))/2=(3+lg3-lg3+1)/2=4/2=2
lgx=2 ⇒ x₂=10²=100. Ответ: x₁=30 x₂=100.